Comparison of Prevalence of Hyperlipidemia, Medical Expenses, Inpatient, Emergency and Outpatient According to the Level of Physical Activity of Korean Adults: A Cross-Sectional Study of 2018 Korea Medical Panel - Byung-Kun Lee (Asian Society of Kinesiology, 2021)
OBJECTIVES The purpose of this study is to compare the difference in the prevalence of hyperlipidemia according to the level of physical activity in adults, and to compare the difference between annual personal medical expenses, hospitalization, emergency and outpatient use depending on the level of physical activity for hyperlipidemia patients. METHODS The 2018 Korea medical panel data was used (14,489 adults and 2,559 Hyperlipidemia). Physical activity was measured with short form of IPAQ and converted to MET-minutes per week. The days of hospitalization, and personal medical expenses were compared, and frequency analysis, logistic regression, ANOVA and chi-square were performed. RESULTS The prevalence of hyperlipidemia based on the inactive group were decreased both minimally active group (OR = 0.94) and the active group (OR = 0.74, p<0.01). Annual personal medical expenses I (p<.01) and II (p<.01) with hyperlipidemia were all showed significant differences depending on the level of physical activity. On active group basis, medical expenses showed slight differences of 3.0 to 3.2% with the minimally activity group, but that of the inactive group were 19.3 ~ 21.7% higher. The annual days of hospitalization were 6.8 ± 7.2 days in activity group, minimally activity group 7.1 ± 7.2 days, inactive group 11.7 ± 26.0 days. There was no significant difference in the annual days of hospitalization and emergency between the three groups. In particular, the annual days of outpatient increased sharply at the inactive group. Participation in physical activity has been shown to have a significant effect on hospitalization and decreasing use of emergency rooms. CONCLUSIONS Hyperlipidemia prevalence was similar to inactive groups and minimally activity groups, and that of activity groups was 0.74. On medical expenses of hyperlipidemia, the activity and minimally activity group was similar, the inactivity group was 19.3 to 21.7% higher. Physical activity was found to have a positive effect on hospitalization and emergency use reduction.